ChemInform Abstract: Powering the Future of Molecular Artificial Photosynthesis with Light‐Harvesting Metallosupramolecular Dye Assemblies. Issue 29 (1st July 2013) - Frischmann, Peter D.; Mahata, Kingsuk; Wuerthner, Frank
Abstract: Review: 139 refs.